2022
DOI: 10.56741/jmsd.v1i01.43
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Contributing to Impulse Buying Behavior of E-Commerce Users

Abstract: Ease of accessing the internet and information technology triggers impulsive buying behavior through increased accessibility to products and services that facilitate the buying process. Through internet facilities by browsing, consumers can feel like window shopping in a mall. This study focuses on the Java-Bali area which is a strategic location in access to products. Data were collected from 273 respondents of E-commerce users using a survey method. Structural Equation Modeling (SEM) modeling technique with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Kocot and Kwasek (2022) ascertain that the key factors influencing consumer purchasing decisions in the online realm are product/service quality, price, and access to product information. Ronaldo et al (2022) found that e-commerce browsing and the big five personality traits influence the desire to make purchases and engage in impulsive buying. Furthermore, the purchase intention of e-commerce consumers is influenced by trust, perceived utility, and affect (Dachyar & Banjarnahor, 2017).…”
Section: Literature Searchmentioning
confidence: 99%
“…Kocot and Kwasek (2022) ascertain that the key factors influencing consumer purchasing decisions in the online realm are product/service quality, price, and access to product information. Ronaldo et al (2022) found that e-commerce browsing and the big five personality traits influence the desire to make purchases and engage in impulsive buying. Furthermore, the purchase intention of e-commerce consumers is influenced by trust, perceived utility, and affect (Dachyar & Banjarnahor, 2017).…”
Section: Literature Searchmentioning
confidence: 99%